2020
DOI: 10.17942/sted.551556
|View full text |Cite
|
Sign up to set email alerts
|

İlkokul Çağindaki̇ Çocuklarda Obezi̇te Görülme Sikliği

Abstract: The objective of the research was to identify the prevalence of obesity in primary school children. Material and Method: The cross-sectional study was conducted among 1526 students at a primary school between October 2016 and May 2017. The data were collected using the student follow-up form. Findings: The mean age of the children was 8.35±1.28 years; of them, 50.2 % were females and 5.2 % were Syrians. 7.7% of the children were found to be overweight and 8.8% of them were obese. A significant difference was n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 4 publications
0
1
0
2
Order By: Relevance
“…Metinoğlu ve ark. 'nın [47] yaptığı çalışmada baba eğitim durumu, aile gelir düzeyine göre BKİ arasında çalışmamıza benzer şekilde fark bulunmamıştır. Yine başka bir çalışmada aşırı kilolu/obez 11-16 yaş arası çocuk ve ergenlerin normal kilolu olan yaşıtlarına göre anne çalışma durumu, anne eğitim durumu, baba eğitim durumu açısından farklılık göstermediği tespit edilmiştir [48].…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Metinoğlu ve ark. 'nın [47] yaptığı çalışmada baba eğitim durumu, aile gelir düzeyine göre BKİ arasında çalışmamıza benzer şekilde fark bulunmamıştır. Yine başka bir çalışmada aşırı kilolu/obez 11-16 yaş arası çocuk ve ergenlerin normal kilolu olan yaşıtlarına göre anne çalışma durumu, anne eğitim durumu, baba eğitim durumu açısından farklılık göstermediği tespit edilmiştir [48].…”
Section: Discussionunclassified
“…Çalışmamızda "her sabah iyi bir kahvaltı yapmayı seviyorum" cümlesine katılmayan çocuk ve ergenlerin oranı %74,5 olarak bulunmuştur. Bu oran sabah kahvaltısı öğününün sıklıkla atlandığını gösteren önceki çalışmalarla uyumludur [47,59,60]. Kahvaltı öğününü atlamak çocuk ve ergenlerde aşırı kilolu olma, obez olma, kötü lipit profili, insülin direnci ve metabolik sendromla ilişkilidir [60].…”
Section: Discussionunclassified
“…Also, negative body image was found to be a prospective predictor of chronic eating problems in adolescence and young adulthood in the same study. In a recent study in Turkey, it has been found that the prevalence of overweight and obesity among primary school children is high and this rate increased with age (Özsoy et al, 2020). Moreover, Sezer (2018) found that childhood obesity is not noticed by Turkish parents they did not perceive obesity as a health threat.…”
Section: Introductionmentioning
confidence: 99%